2023
DOI: 10.1117/1.jnp.17.036006
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning aids simultaneous structure–material design discovery: a case study on designing phase change material metasurfaces

Abstract: .The capabilities of modern precision nanofabrication and the wide choice of materials [plasmonic metals, high-index dielectrics, phase change materials (PCM), and 2D materials] make the inverse design of nanophotonic structures such as metasurfaces increasingly difficult. Deep learning is becoming increasingly relevant for nanophotonics inverse design. Although deep learning design methodologies are becoming increasingly sophisticated, the problem of the simultaneous inverse design of structure and material h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Compared to the data published in [40], although the increase in the drift mobility values is not much pronounced, for the first three oscillators eV, the plasmon frequency and free electron concentration are highly increased 12.2 and 150, 4.1 and 17.5 and 1.3 and 1.6 times, respectively. These features which are reached via pulsed laser assisted crystallinity of the films within one second make the material more effective in optoelectronic technology [55][56][57].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the data published in [40], although the increase in the drift mobility values is not much pronounced, for the first three oscillators eV, the plasmon frequency and free electron concentration are highly increased 12.2 and 150, 4.1 and 17.5 and 1.3 and 1.6 times, respectively. These features which are reached via pulsed laser assisted crystallinity of the films within one second make the material more effective in optoelectronic technology [55][56][57].…”
Section: Resultsmentioning
confidence: 99%
“…They considered a vast design space consisting of four commonly used phase change materials and an arbitrarily specifiable polygonal meta-atom They found that a deep neural network can accurately predict optical spectra in this design space and can be used in a surrogate-optimization setup to achieve the inverse design of active metasurfaces. Overall, the study demonstrated the potential of DL-assisted approaches in designing complex nanophotonic structures [157]. There are a few more papers [158,159] that discuss the application of deep learning (DL) for the inverse design of PCM-based metasurfaces.…”
Section: Using Inverse Design Approachmentioning
confidence: 85%